QAWAID FIQHIYYAH(Korelasi, Urgensi Dalam Istinbath Hukum) - Y. Sonafist (INTELIGENSIA MEDIA, 2023)
Al-qawaid al-fiqhiyyah is a general rule covering a number of fiqh issues and through it can be known the law of fiqh issues that are within its scope. Al-qawaid al-fiqhiyyah which was formulated by the scholars which was not directly adopted and based on texts cannot be used as an argument in establishing Islamic law. Because, it is illogical to make something which is a collection of a number of furû' (fiqh) issues as the proposition of the syara' proposition. However, if the fiqh rules are directly based on and based on the arguments from the Qur'an and Sunnah (nash), they can be used as evidence in establishing law.